The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2337/db07-0193
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Ingestion Fails to Inhibit Hypothalamic Neuronal Activity in Patients With Type 2 Diabetes

Abstract: OBJECTIVE-The hypothalamus plays a critical role in the regulation of energy balance and fuel flux. Glucose ingestion inhibits hypothalamic neuronal activity in healthy humans. We hypothesized that hypothalamic neuronal activity in response to an oral glucose load would be altered in patients with type 2 diabetes.RESEARCH DESIGN AND METHODS-In this randomized, single blind, case-control study, 7 type 2 diabetic men (BMI 27.9 Ϯ 2.0 kg/m 2 ) and 10 age-matched healthy men (BMI 26.1 Ϯ 3.2 kg/m 2 ) were scanned tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
54
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 21 publications
5
54
2
Order By: Relevance
“…In contrast, previous studies by Smeets and colleagues [4][5][6] have shown a prolonged decrease in signal in the hypothalamus after oral glucose, continuing for at least 30 min after ingestion. Our data tend to support the results of Smeets and colleagues and contradict the results of Liu and colleagues, in that they show a prolonged rather than shortlived signal decrease after ingestion of glucose.…”
contrasting
confidence: 65%
See 1 more Smart Citation
“…In contrast, previous studies by Smeets and colleagues [4][5][6] have shown a prolonged decrease in signal in the hypothalamus after oral glucose, continuing for at least 30 min after ingestion. Our data tend to support the results of Smeets and colleagues and contradict the results of Liu and colleagues, in that they show a prolonged rather than shortlived signal decrease after ingestion of glucose.…”
contrasting
confidence: 65%
“…Previous experiments using a glucose load have suggested that it is possible in humans to identify changes in the BOLD signal from areas within the hypothalamus [2][3][4][5][6]; however, the results have been contradictory.…”
mentioning
confidence: 97%
“…Functional MRI scans detecting blood oxygen level-dependent signals showed hypothalamic signaling changes in response to glucose infusions (86 -88). These changes were diminished or absent in obese (89) and T2DM subjects (88). In addition, a link between CNS insulin and peripheral glucose metabolism was suggested by studies of intranasal insulin.…”
Section: Evidence From Human Studies Supporting Cns Regulation Of Metmentioning
confidence: 97%
“…Glucose levels can modulate neural firing in the hypothalamus (22), and the presence of diabetes (1,44) as well as hyperglycemia (31) has been found to interfere with hypothalamic signaling. However, since neural signals may be necessary only in the preprandial rise of ghrelin (46), the presence of disrupted neural regulation of satiety is therefore unlikely to explain the absence of a postprandial decline in ghrelin levels in our study.…”
Section: E229mentioning
confidence: 99%